Variation of features of interframe dependent HMM for speech recognition - Harte, Naomi (My University, 1998)
The effects are explored of using different dynamic features in conjunction with an HMM that permits a dependency on both preceeding and succeeding frames. In particular, features which capture dynamic information are vaned in the interframe dependent HMM. A recognition accuracy of 93.9% for the Connex speaker-independent E-set was obtained using tied states
PUBLISHED
Keywords: Electronic & Electrical Engineering; Digital Engagement